Persisting CAM deformity is associated with early cartilage degeneration after Slipped Capital Femoral Epiphysis: 11-year follow-up including dGEMRIC. Issue 4 (April 2018) - Örtegren, J.; Peterson, P.; Svensson, J.; Tiderius, C.J.
Summary: Objective: Slipped capital femoral epiphysis (SCFE) in adolescence is associated with increased risk of future osteoarthritis (OA). The purpose of this study was to study clinical and radiographic risk factors for early cartilage degeneration after SCFE. Design: 22 patients (44 hips) (mean age 24 years, range 18–27) treated with in situ fixation (The Hansson hook-pin) for stable SCFE on average 11 years previously were investigated. Cartilage status was assessed with delayed gadolinium-enhanced magnetic resonance imaging of cartilage (dGEMRIC). The alpha angle, reflecting femoroacetabular impingement (FAI), and the original slip angle were measured. Clinical outcome was assessed with the Copenhagen hip and groin outcome score (HAGOS) and clinical examination. Results: The dGEMRIC index was lower in SCFE hips than unaffected hips 456 ms (CI 419–493) vs 521 ms (CI 476–567) ( P = 0.03). The difference was larger (mean 21 ms) in anterior than posterior regions of the hip ( P = 0.038). The alpha angle was higher in SCFE hips, 61.5° (CI 53.9–69.1) vs 45.6° (CI 43.6–47.6), ( P < 0.001). The alpha angle, but not the original slip angle, correlated negatively with the dGEMRIC index ( R = −0.40, P = 0.046). There was a positive correlation between HAGOS and the dGEMRIC-index ( R = 0.41, P = 0.012). Conclusions: Early cartilage degeneration after SCFE seems related to persisting FAI in adulthood, rather than the initial slip severity. The correlation between dGEMRIC and HAGOS indicates a clinical relevance of the MRI findings. Our results suggest that FAI after SCFE should be evaluated already after physeal closure in order to predict and possibly prevent future OA development.